Dukungan Keluarga dengan Kecemasan Pasien Pre Operasi Sectio Caesaria - Dedi Kurniawan; Egy Mulyadi; Anggun Fajar Ramadhani; Asep Suryadin (Journal of Telenursing (JOTING), 2026)
This study aims to analyze the relationship between family support and preoperative anxiety levels in patients undergoing cesarean section at Primaya Hospital Sukabumi. The study used a quantitative design with a cross-sectional approach, involving 32 patients selected using a total sampling technique. The results showed that most respondents reported high levels of family support, and descriptive anxiety was mild to moderate. However, statistical analysis revealed no significant relationship between family support and anxiety levels (r = -0.235; p = 0.196). In conclusion, family support has a weak and insignificant negative relationship with preoperative anxiety, necessitating a holistic approach to managing patient anxiety.   Keywords: Family Support, Anxiety, Preoperative, Cesarean Section